Design and Music: creating an audiovisual bridge between generation Z and the legacy of Raul Seixas - Pereira Melo, Camila; Fernandes, Fabiane (DAT Journal, 2024)
Music and design possess the ability to convey messages through aesthetic experiences. When combined, they give rise to audiovisual design, widely present in the music industry and dedicated to creating impactful narratives with graphic elements. Animation, one form of audiovisual design, brings static images to life and raises a relevant question: why does Generation Z show little interest in Brazilian music from past decades? To investigate this relationship, we developed an animation based on a song by Raul Seixas, using the animation production methodology proposed by Winder and Dowlatabadi (2011), adapted with design tools. Simultaneously, we conducted a survey to collect data on social media consumption, music preferences, and perceptions of the animation. The results helped establish connections between the consumption of music and audiovisuals and the perception of the animation across different age groups. This article explores the synergy between sound and image to discover how we can spark Generation Z’s interest in the richness of Brazilian music from the past.